B7-H3 Immune Checkpoint Protein in Human Cancer - Flem-Karlsen, Karine; Fodstad, Øystein; Nunes-Xavier, Caroline E. (Current Medicinal Chemistry, 2020)
B7-H3 belongs to the B7 family of immune checkpoint proteins, which are important regulators of the adaptive immune response and emerging key players in human cancer. B7-H3 is a transmembrane protein expressed on the surface of tumor cells, antigen presenting cells, natural killer cells, tumor endothelial cells, but can also be present in intra- and extracellular vesicles. Additionally, B7-H3 may be present as a circulating soluble isoform in serum and other body fluids. B7-H3 is overexpressed in a variety of tumor types, in correlation with poor prognosis. B7-H3 is a promising new immunotherapy target for anti-cancer immune response, as well as a potential biomarker. Besides its immunoregulatory role, B7-H3 has intrinsic pro-tumorigenic activities related to enhanced cell proliferation, migration, invasion, angiogenesis, metastatic capacity and anti-cancer drug resistance. B7-H3 has also been found to regulate key metabolic enzymes, promoting the high glycolytic capacity of cancer cells. B7-H3 receptors are still not identified, and little is known about the molecular mechanisms underlying B7-H3 functions. Here, we review the current knowledge on the involvement of B7-H3 in human cancer.
Keywords: body fluids